Analytical Approach of Laser-Induced Breakdown Spectroscopy to Detect Elemental Profile of Medicinal Plants Leaves - Abdul Jabbar; Mahmood Akhtar; Shaukat Mehmood; Koo Hendrick Kurniawan; Rinda Hedwig; Muhammad Aslam Baig (Universitas Gadjah Mada, 2019)
Laser ablation chemical and spectroscopic studies of Calotropis procera, Chenopodium ambrosioides, and Nerium indicum leaves was performed using 1064 nm Nd: YAG laser in air at different pressure and time delay. These medicinal plant’s leaves are used by local people for different diseases. The knowledge of medicinal and toxic metals in these plants is very important. We have presented time-resolved studies of different elements and how their lives change with different delay time. C, H, Si, Al, Fe, Cu, Ca, Mg, Na, K, N, O, Sr and Ba have been detected in all the three samples with a molecular form of Carbon and Nitrogen band. We have detected C, H, N, and O as a major element while, Fe, Cu, Mg, K and Ca as essential medicinal metals with other trace elements such as Si, Sr, Al and Ba in all the three plants leaves. We present 1 µs delay time is the best time for elements lifetime in time resolved studies. The behaviour of intensity with different pressures was also studied and it was concluded that 7 torr was the best pressure for the maximum value of intensity. In particular, the electron density and the temperatures of the plasma were reported. The temperature was calculated from the well-known Boltzmann plot method and electron density was estimated from the stark broadened profile of the Hα line.